Role of CB-NAAT in diagnosing Mycobacterial tuberculosis and rifampicin resistance in tubercular peripheral lymphadenopathy - Krishna Gopal Singh; Sanjay Tandon; S.T Nagdeote; Kapil Sharma; Ajay Kumar (International Journal of Medical Research and Review, 2017)
Introduction: Diagnosis of Extra Pulmonary TB (EPTB) remains a challenge. This study assessed the applicability of CB-NAAT in early diagnosis of EPTB, especially peripheral lymphadenopathy and early identification of MDR-TB in TB lymphadenopathy.Material & Method: This was a prospective, cross sectional study, carried out on all patients of age group 10 to 80 years, who were suspected cases of tubercular peripheral lymphadenopathy, visiting the OPD of the Department of Pulmonary Medicine, People’s Hospital, Bhopal, over a period of 1 year 6 months. FNA of peripheral lymph nodes of 57 patients was sent for cytology and CB-NAAT.Result: This study showed that statistical difference in diagnostic yield of FNAC (47/57 i.e. 82.4%) and CB-NAAT (44/57 i.e. 77.19%) in tubercular peripheral lymphnode sample was not significant. This implies that there was not much difference in these two test results. There was no rifampicin resistance in the population studied.Conclusion: CB-NAAT did not diagnose more cases of TB-LN than FNAC.